Serum-free corneal organ culture medium (SFM) but not conventional minimal essential organ culture medium (MEM) protects human corneal endothelial cells from apoptotic and necrotic cell death. Issue 1 (24th October 2010) - Jäckel, Thekla; Knels, Lilla; Valtink, Monika; Funk, Richard H W; Engelmann, Katrin
Abstract : Aim: To evaluate the influence of organ culture media on corneal endothelial cell survival. Methods: The human corneal endothelial cell line HCEC-12 was cultured in five different media: human corneal endothelial cell (HCEC) growth medium (F99HCEC ), standard minimal essential corneal organ culture medium (MEM)+2% fetal calf serum (FCS), MEM+5% FCS, and humanised, endothelial serum-free medium (SFM) (with and without antibiotics). A portion of the cells was treated with 0.5 μmol/l staurosporine and examined for signs of apoptosis by assessing mitochondrial membrane polarisation state (intravital JC-1 staining), by YO-PRO-1 and propidium iodide staining, by determining fragmentation of nuclei by sub-G1 DNA content, by immunocytochemistry for cleaved caspase-3, cleaved caspase-8, Bcl2-associated X protein (Bax) and B-cell lymphoma 2 (Bcl-2), and by western blotting for cleaved caspase-3 and cleaved poly (ADP-ribose) polymerase (PARP). Results: The number of apoptotic cells in untreated control cultures was significantly higher in MEM compared with F99HCEC and SFM. Staurosporine treatment induced apoptosis in all tested cultures to varying degrees. Cells cultured in MEM showed stronger staining for cleaved caspase-3, cleaved caspase-8, Bax, Bcl-2 and cleaved PARP, increased sub-G1 DNA content, more propidium iodide- and YO-PRO-1-positive cells, and more mitochondria with depolarised membranes. All parameters were significantly higher in MEM compared with F99HCEC and SFM. SFM cultures were significantly less susceptible to cell stress. Conclusion: SFM is superior to MEM in promoting HCEC survival.